The chemical challenges in "Deepwater" - Craddock, Henry (Engineering cases, 2013)
In the last 10 years there has been a greatly increased activity in the Oil and Gas industry in the development of, and production from Deepwater assets. These Deepwater fields present unique engineering and chemical challenges to ensure production security and continuous flow of hydrocarbons.